Effects of Plastic and Acrylate Polymers on the Release Profile of Ambroxol Hydrochloride Controlled Release Pellets - Ahmed, Ishtiaq; Roni, Monzurul Amin; Kibria, Golam; Islam, Muhammad Rashedul; Rahman, Md Habibur (Dhaka University Journal of Pharmaceutical Sciences, 2009)
The effects of Ammonio Methacrylate copolymer dispersion (Eudragit® NE 30 D) and Polyvinyl Acetate dispersion (Kollicoat® SR 30 D) are compared on the in vitro release of Ambroxol Hydrochloride from coated pellets in the current study. The nuclei pellets were manufactured by Extrusion-Spheronization with the drug, microcrystalline cellulose, lactose, maize starch, and hydroxypropyl methylcellulose followed by fluid bed coating. Dissolution study of coated pellets was performed with USP Type-II apparatus in acidic (0.1N HCl for 1 h) and buffer (phosphate buffer, pH 6.8 for 11 h) media to simulate gastrointestinal environment. The release profile of drug from two types of polymers were distinct and drug release was sustained longer by Polyvinyl Acetate film than Acrylate polymer. Key words: Aqueous coating, Eudragit® NE 30D, Kollicoat® SR 30D, release kinetics, pellets, extrusion-spheronization doi: 10.3329/dujps.v7i2.2176 Dhaka Univ. J. Pharm. Sci. 7(2): 181-186, 2008 (December)